The Role Of Nurse-Led Interventions In Managing Chronic Diseases: A Systematic Review (The Review of Diabetic Studies, 2024)
Non-communicable chronic diseases like cardiovascular disease, diabetes, and chronic respiratory diseases continue to be significant health challenges worldwide and a burden to health care systems, impacting millions of individuals. The role of nurses in the treatment of these conditions is vital and is becoming widely acknowledged. The systematic review tested the efficacy of nurse-led interventions to manage chronic diseases.The searches were performed in large databases, such as PubMed, CINAHL, Scopus, Web of Science, or Cochrane Library. Intervention types involving nurse as leaders were chosen, with randomized and quasi-experimental designs being predominant. Two independent reviewers extracted the data and assessed the biasness of the data, synthesized in a narrative and in a meta-analysis where applicable.Findings indicated that nurse-led interventions, compared to physician-led or usual care, often were able to achieve better clinical outcomes (blood pressure and glycemic control) in ambulatory settings. Quality of life, satisfaction and self-management patient-reported outcomes also improved. But others were associated with a high risk of bias or inconsistent findings.In general, interventions conducted by nurses are effective in the diagnosis of chronic diseases. Further studies are needed to optimize the type of interventions, evaluate their cost-effectiveness in the long term, and minimize heterogeneity to enhance evidence base.